Changes in Hyolaryngeal Movement During Swallowing in the Lateral Decubitus Posture - Byung-Mo Oh; Jae Hyun Lee; Han Gil Seo; Woo Hyung Lee; Tai Ryoon Han; Seoung Uk Jeong; Ho Joong Jeong; Young-Joo Sim (Annals of Rehabilitation Medicine, 2018)
Objective To investigate the differences in hyolaryngeal kinematics at rest and during swallowing in the upright sitting (UP) and the lateral decubitus (LD) postures in healthy adults, and delineating any potential advantages of swallowing while in the LD posture. Methods Swallowing was videofluoroscopically evaluated in 20 healthy volunteers in UP and LD postures, based on the movements of hyoid bone, vocal folds, and the bolus head. Parameters included the Penetration-Aspiration Scale (PAS), horizontal and vertical displacement, horizontal and vertical initial position, horizontal and vertical peak position, time to peak position of the hyoid bone and vocal folds, and pharyngeal transit time (PTT). Results Nine participants were rated PAS 2 in the UP and 1 was rated PAS 2 in the LD (p=0.003) at least 1 out of 3 swallows each posture. The hyoid and vocal folds showed more anterior and superior peak and initial positions in the LD. In addition, swallowing resulted in greater vertical and smaller horizontal displacement of the hyoid in LD posture compared with UP. Time to peak position of the hyoid was shorter in LD. The maximal vertical and horizontal displacement of the vocal folds, and PTT were comparable between postures. Conclusion The results showed that the peak and initial positions of the hyoid and larynx and the pattern of hyoid movement varied significantly depending on the body postures. This study suggests that the LD posture was one of the safe feeding postures without any increased risk compared with UP posture.